2006
DOI: 10.1002/cbf.1335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin K1 supplementation on vascular responsiveness and oxidative stress in a rat femoral osteotomy model

Abstract: The main function of vitamin K1 is to act a co-factor for gamma-glutamyl carboxylase. However, it has also been shown to lessen oxidative stress. This study was aimed to evaluate the effect of vitamin K1 supplementation on vascular responsiveness and oxidative status in rats that underwent femoral osteotomy. Twenty-four male rats were divided into three groups to serve as sham, osteotomy and vitamin K1 groups. Indices of oxidative stress (catalase), and oxidative damage (malondialdehyde) were analysed in eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Vitamins such as vitamin E and C are known for their antioxidative effects. A few studies have also reported that vitamin K may have antioxidative effects (Mukai, Morimoto, Kikuchi, & Nagaoka, 1993;Tasatargil et al, 2006), but to the best of our knowledge the ability of vitamin K to prevent oxidation in drinking yoghurt with or without oil has never been investigated. Since vitamin K is a naturally occurring lipid-soluble substance, it may be an attractive natural alternative to synthetic antioxidants.…”
Section: Introductionmentioning
confidence: 96%
“…Vitamins such as vitamin E and C are known for their antioxidative effects. A few studies have also reported that vitamin K may have antioxidative effects (Mukai, Morimoto, Kikuchi, & Nagaoka, 1993;Tasatargil et al, 2006), but to the best of our knowledge the ability of vitamin K to prevent oxidation in drinking yoghurt with or without oil has never been investigated. Since vitamin K is a naturally occurring lipid-soluble substance, it may be an attractive natural alternative to synthetic antioxidants.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, calcium intake may aff ect oxidative stress through calcium transport and signaling line [ 41 ] . Although vitamin K is not a classical antioxidant, previous studies suggest that vitamin K1 could act as a potent antioxidant through the formation of hydroxyl radicals during the peroxidation reaction [ 42 ] .…”
mentioning
confidence: 99%